2019
DOI: 10.1210/jc.2019-00677
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Menopausal Vasomotor Symptoms With Fezolinetant, a Neurokinin 3 Receptor Antagonist: A Phase 2a Trial

Abstract: Context The thermoregulatory center in the hypothalamus is stimulated by neurokinin 3 receptor (NK3R) activation and inhibited by estrogen-negative feedback. This balance is disrupted in menopause, producing vasomotor symptoms (VMSs). Objective To evaluate safety and efficacy of the NK3R antagonist fezolinetant in menopausal VMSs. Design Twelve-week, double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 49 publications
1
102
0
1
Order By: Relevance
“…These change dramatically in postmenopausal women, in whom they can generate hot flushes [39]. In this subpopulation of neurons, in particular, neurokinin B and its receptor NK3R have been implicated in the induction of hot flushes in healthy women that are typical in location and duration of postmenopausal hot flushes [40,41]. In order to gain more insights into the mechanism of action of Serelys V R on neurons, the effect of PureCyTonin V R on the uptake of [ 3 H]-serotonin into rat cortical synaptosomes was analyzed.…”
Section: Mechanism Of Action Of Serelys V Rmentioning
confidence: 99%
“…These change dramatically in postmenopausal women, in whom they can generate hot flushes [39]. In this subpopulation of neurons, in particular, neurokinin B and its receptor NK3R have been implicated in the induction of hot flushes in healthy women that are typical in location and duration of postmenopausal hot flushes [40,41]. In order to gain more insights into the mechanism of action of Serelys V R on neurons, the effect of PureCyTonin V R on the uptake of [ 3 H]-serotonin into rat cortical synaptosomes was analyzed.…”
Section: Mechanism Of Action Of Serelys V Rmentioning
confidence: 99%
“…Elegant opticogenetic labeling experiments have shown that the stimulation of these thermoregulatory neurons by KNDy neurons is mediated by neurokinin B acting though NK3 receptors ( 15 ). Three compounds with NK3R antagonist activity have now been shown to have striking efficacy in reducing menopausal VMS ( 9 , 16–18 , 21 ), supporting the development of NK3R antagonists as a highly effective nonhormonal class of medicine. In relation to the possible therapeutic potential in a range of sex hormone–dependent conditions through the inhibition of GnRH secretion, it is noteworthy that the suppression of LH and testosterone was maximal at about 6 to 12 hours, with recovery thereafter, even with higher doses, despite the continuing presence of effective serum concentrations of SJX-653 for at least 48 hours.…”
Section: Discussionmentioning
confidence: 94%
“…Fezolinetant was next evaluated in patients with VMS associated with menopause in phase II studies. These included a 12week double-blind proof-of-concept phase IIa study conducted in eight Belgian clinics from September 2015 to October 2016 (EudraCT 2015-002578-20), in which healthy postmenopausal women 40-65 years of age with moderate/severe VMS (≥49 episodes/week) were randomized 1:1 to fezolinetant 90 mg BID or placebo [62]. In addition, a 12-week, randomized, placebocontrolled, double-blind dose-ranging phase IIb study (VESTA; [ClinicalTrials.gov NCT03192176]) was conducted at 51 sites in the US from July 2017 to September 2018 in postmenopausal women 40-65 years of age with moderate/severe VMS (≥50 episodes/week) who were randomized to fezolinetant 15, 30, 60, or 90 mg BID or 30, 60, or 120 mg QD or placebo [63].…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…In the phase IIa study, at peak drug levels (3 h postdose), fezolinetant decreased plasma LH by 49.8% relative to baseline vs 16.4% with placebo [62]. Fezolinetant showed little impact on plasma levels of estradiol, FSH, and sex hormonebinding globulin (SHBG).…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%